Data for Tracing the botanical origins of UK heather honey by relative quantification of plant DNA - Dodd, Sophie; Anastasiadi, Maria; Kevei, Zoltan; Karimi, Zahra; Kumar, Jane Jennifer Suresh; Koidis, Anastasios (Cranfield University, 2025)
Heather honey is an important honey type produced in the UK, valued for its unique flavour, thixotropic texture and health promoting properties. Botanical authentication can be challenging due to the natural variability in honey composition and typical pollen analysis relies heavily on expert knowledge. As an alternative, real-time PCR (qPCR) can be a rapid and robust method to identify floral species in honey. Therefore, species-specific markers for Calluna vulgaris and Erica cinerea were developed and used to quantify 266 honey samples relative to the plant trnL P6 loop. The method classed 94% of 234 heather honeys as containing > 3% heather DNA, with 68% classified as dominant (> 45%) for ling heather origin. Moreover, high specificity was achieved with negligible amplification in the 32 non-heather honeys. Our qPCR method offered comparable results to melissopalynology, DNA metabarcoding and digital PCR, showing potential as an alternative and accessible method for botanical authentication of heather honeys.
Date of data collection: 2021 - 2025 Geographic location of data collection: Cranfield University, College Road, Cranfield, MK43 0AL, UK. This repository contains the following data files: a) a.honey_Cq_RQ_DODD2025.csv :a dataset containing qPCR amplification (Cq value) for all honey samples , relative quantification calculation and the resulting class group. b) b.BLAST_ling_DODD2025.pdf :complete in silico analysis of the Calluna vulgaris marker using PrimerBLAST. c) c.BLAST_bell_DODD2025.pdf :complete in silico analysis of the Erica cinerea marker using PrimerBLAST. DATA-SPECIFIC INFORMATION FOR: [a.honey_Cq_RQ_DODD2025.csv] Number of variables: 15 Number of cases/rows: 271 Variable List: The Cq values from reaction 1-3 for trnL_P6 marker, The Cq values from reaction 1-3 for CV_trnL marker, The Cq values from reaction 1-3 for EC_trnL marker, The relative quantity (RQ) of ling, The relative quantity (RQ) of bell, The standard deviation (SD) of RQ of ling, The SD of RQ of bell, the final class of ling, the final class of bell. Missing data codes: na: not amplified, N/A: not applicable Specialized formats or other abbreviations used: ling: Calluna vulgaris plant, bell: Erica cinerea plant, final class calculated according to RQ value for ling or bell (dominant: > 0.45, secondary: 0.16 – 0.45, important minor: 0.03 – 0.16, trace: 0.03 – 0.01, sporadic: 0.01 – 0.001 and none: <0.001) Grant: BB/T008776/1
Keywords: Calluna vulgaris; honey; authentication; trnL P6; relative quantification; qPCR; metabarcoding